Study of Benefit Economic Value of Post Coal Mining Land as Carbon Absorber at PT Sungai Pangean Jaya - Ridho Yovanda; Restu Juniah; Anna Yulianita (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Ex-mining land becomes an important thing to pay attention to after all or part of mining activities end in order to provide benefits for current and future generations. One of the efforts that can be done is to plant ex-mining land with plants such as oil palm. Oil palm plants, apart from providing the benefits of their harvest, can be sold, but also useful as a carbon sink. The purpose of this study is to calculate the economic value of the benefits of the ex-coal mining land of PT Sungai Pangean Jaya as a carbon sink. The data needed to achieve this goal are carbon prices, interest rates, the area of revegetated areas, and the carbon sequestration capacity of oil palm plantations. The calculation results show that the economic value for the years 2012-2026 that can be obtained is IDR 9,458,184,656.75, with the benefit value at the price in 2022 (present value in 2022) is IDR 9,960,926,612.01. Lahan bekas tambang menjadi hal yang penting untuk diperhatikan setelah seluruh atau sebagian kegiatan pertambangan berakhir agar memberikan kebermanfaatan bagi generasi sekarang dan di masa mendatang. Salah satu upaya yang dapat dilakukan adalah dengan menanami lahan bekas tambang dengan tanaman seperti kelapa sawit. Tanaman kelapa sawit selain memberikan kebermanfaatan hasil panenya dapat dijual, namun juga bermanfaat sebagai penyerap karbon. Tujuan penelitian ini adalah menghitung nilai ekonomi manfaat manfaat lahan bekas tambang batubara PT Sungai Pangean Jaya sebagai penyerap karbon. Data yang dibutuhkan untuk mencapai tujuan tersebut adalah harga karbon, suku bunga, luasan area yang direvegetasi, dan kemampuan serap karbon tanaman sawit. Hasil perhitungan menunjukkan bahwa nilai ekonomi untuk tahun 2012-2026 yang bisa diperoleh adalah sebesar Rp 9.458.184.656,75, dengan nilai manfaat pada harga tahun 2022 (present value tahun 2022) adalah senilai Rp 9.960.926.612,01.